2023
DOI: 10.1101/2023.02.03.527092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FarmGTEx TWAS-server: an interactive web server for customized TWAS analysis in both human and farm animals

Abstract: Transcriptome-wide association study (TWAS) is a powerful strategy for elucidating the molecular mechanisms behind the genetic loci of complex phenotypes. However, TWAS analysis is still daunting in many species due to the complication of the TWAS analysis pipeline, including the construction of the gene expression reference panel, gene expression prediction, and the subsequent association analysis in the large cohorts of genome-wide association study (GWAS). Farm animals are major protein sources and biomedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…To enhance the understanding of hologenome interactions in complex traits, we used GWA summary statistics to perform TWAS analysis and gene set enrichment analysis (GSEA) by using the FarmGTEx TWAS-server ( , accessed on 5 July 2023) [ 78 ]. Firstly, the GWAS imputation module imputed the SNPs from summary statistics according to eQTL mapping of cattle and pig reference genomes.…”
Section: Methodsmentioning
confidence: 99%
“…To enhance the understanding of hologenome interactions in complex traits, we used GWA summary statistics to perform TWAS analysis and gene set enrichment analysis (GSEA) by using the FarmGTEx TWAS-server ( , accessed on 5 July 2023) [ 78 ]. Firstly, the GWAS imputation module imputed the SNPs from summary statistics according to eQTL mapping of cattle and pig reference genomes.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained a variety of network categories, including co-expression, physical interaction, genetic interaction, shared protein domains, co-localization, pathway, and enriched genes in the network. (3) The Farm animal Genotype-Tissue Expression TWAS-Server (FarmGTEx TWAS-Server, , accessed on 12 December 2022) [ 27 ] provides the TPM (transcript per million) of numerous genes across pig tissues. The TPM data were used to evaluate the correlation of gene expression between NR6A1 , PAPPA2 , PIK3C2B , and FASN in different pig tissues.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of the kinship index based selection (KIS) method is limited by the accuracy and coverage of functional genes in pigs. Previous studies have reported on the association of functional genes with traits in pigs, and databases, such as The Farm animal Genotype-Tissue Expression TWAS server ( ) [ 18 ] and PigVar [ 19 ], exist which combine non-redundant variations and evolutionary selective scores. Results from the simulation study indicated that the mating method used may impact selection by the KIS method and that the truncated selection method used may not be the most optimal.…”
Section: Limitations and The Future Of Applying The Kis Methodsmentioning
confidence: 99%